Analysis of GDP Trends and Inequalities in Vietnam’s Provinces and Groups of Provinces - Vu, Xuan-Binh; Nghiem, Son (Asian Journal of Empirical Research, 2016)
Our recent paper (Vu et al., 2016) applied the Phillips and Sul’s method (2007, 2009) and found that the 61 provinces of Vietnam were formed in five convergence sub-groups. This current paper identifies trends and patterns of inequality in provincial GDP per capita of each sub-group of provinces in Vietnam during the period 1990-2011. It also analyses the growth path of each province compared with that of the reference economy [Ho Chi Minh City (HCMC) and the national average]. The results show that there were the downward trends of inequality in GDP per capita of each sub-group. Also, during the period 1990-1994, most provinces diverged from HCMC but during the period 2004-2011, all provinces tended to converge to it. However, there were few poorest provinces, which tend to be located in geographically and economically isolated regions of Vietnam. This paper analyses main characteristics of provinces and key factors affecting the trends and patterns of disparities in GDP per capita of each sub-group. Furthermore, several policy implications are discussed.